Transforming construction in emerging economies: overcoming barriers to the adoption of industrialized building systems - Ermias A. Amede; Asregedew K. Woldesenbet; Astatike K. Bahiru; Fekadu T. Tibebu; Leule M. Hailemariam (Discover Applied Sciences)
Abstract Purpose This study examines the adoption of Industrialized Building Systems (IBS) in emerging economies, with a particular focus on Ethiopia. IBS is a modern construction approach that combines prefabrication, automation, and off-site manufacturing to improve efficiency, minimize waste, and accelerate project delivery. The study explores key barriers within Ethiopia’s cultural and economic landscape and evaluates the factors affecting large-scale implementation. While IBS has been widely adopted in developed countries, its integration in emerging economies remains limited, highlighting a critical gap in understanding the practical challenges of its adoption. Design/methodology/approach The study employed a survey with purposive sampling from key stakeholders. The data was analyzed through Factor Analysis to identify relationships between variables, with Cronbach’s alpha assessing reliability. Findings Five main barriers were identified: (1) lack of skills, (2) logistical inefficiencies, (3) financial constraints, (4) market fragmentation, and (5) limited R&D investment. These challenges delay projects, increase costs, and hinder innovation. The study suggests solutions like enhanced training, improved supply chain management, innovative financing models, and increased R&D investment. Limitations/Implications This study's focus on IBS professionals limits its generalizability to the broader industry context. Further research is needed to explore factors affecting IBS adoption in emerging economies. Practical implications Targeted training, infrastructure investments, innovative financing models, and R&D investment can address key barriers and accelerate IBS adoption, supporting sustainable housing development and global urbanization goals. Originality/Value This study offers a unique perspective on IBS adoption in emerging economies, using Ethiopia as a case study. It highlights how cultural and economic factors (limited capital and fragmented markets) hinder IBS adoption. Addressing these issues, the research fills a gap in the literature and provides a roadmap for overcoming challenges with global implications for construction practices and policy.